IMPLEMENTASI PERATURAN BUPATI NOMOR 30 TAHUN 2019 TENTANG ROAD MAP REFORMASI BIROKRASI PEMERINTAH KABUPATEN PONOROGO TAHUN 2019-2021 DI DINAS KOMUNIKASI INFORMATIKA DAN STATISTIK KABUPATEN PONOROGO - Dian Indriasari Kusuma Dewi (Master of Public Administration, Universitas Slamet Riyadi, 2021)
The lack of an active role in implementing policies, lack of human resources andbudget, as well as the availability of facilities and infrastructure were the causes ofthe inadequate implementation of bureaucratic reform in the Department ofCommunication, Informatics and Statistics, Ponorogo Regency. However, overallthe implementation of bureaucratic reform has been going well. It only needs anincrease and development of the quality and quantity of human resources. Inaddition, the availability of a budget and improvement of facilities andinfrastructure to support the realization of the goals and objectives of bureaucraticreform.Keywords: Communication, Resources, Disposition, Bureaucratic Struc